Dna Barcoding Of The Family Scombridae In Malaysia And Phylogeography And Population Structure Of The Indian Mackerel, Rastrelliger Kanagurta For Sustainable Fisheries - Akib, Noor Adelyna Mohammed (2013)
This research was conducted to develop a molecular systematic identification of the commercially important family Scombridae as well as to understand the phylogeography and phylogenetics of a member species, the Indian mackerel, Rastrelliger kanagurta for sustainable fisheries in Malaysian waters. DNA barcoding based on the mitochondrial cytochrome oxidase subunit I gene, widely known as the barcoding gene successfully identified and delineated 14 species of the family Scombridae sampled in Malaysian waters. The phylogeography and population structure of the pelagic Indian mackerel, R. kanagurta was also investigated among 19 Malaysian populations and one population each from Thailand, Vietnam, Indonesia (Southeast Asian region) and an Iranian population (West Indian Ocean-WIO) using mitochondrial cytochrome b gene analysis. A parallel investigation was conducted on 11 Malaysian populations and an Iranian population based on eight newly developed microsatellite markers. In this study, the next generation sequencing platform, Ion Torrent PGMTM was used to generate a partial genome survey sequence (GSS) dataset to develop microsatellite markers from R. kanagurta genomic DNA. The data generated included a total of 399,794 sequence reads (81.29 Mbp) of which 16,209 sequence reads were successfully assembled, producing 327 contigs averaging 677 bp in length in addition to the single sequence repeats (SSR) markers.